(Un)Credible citizen: citizenship dispossession, documents and the politics of the rule of law. - Bhat, Mohsin Alam (Journal of Ethnic & Migration Studies, 2024)
This article explores how states mobilise ideologies of the rule of law to legitimise, facilitate and obscure human rights violations, especially in the context of citizenship and migration. There is a global pattern of states using ostensibly legal means to undermine citizenship status of vulnerable minorities. In several national contexts, the invocation of the rule of law and the use of legal identity documents are interlocked. States have relied on the regimes of documentary citizenship as the legal face of citizenship deprivation. This article studies India's north-eastern state of Assam – one of the most striking instances of this pattern – where bureaucratic practices of citizenship adjudication have threatened the citizenship status of more than 3 million people. It shows that despite being centred around them, the administrators of documentary citizenship routinely disregard identity documents in their everyday functioning. It argues that India's ethnicised politics towards immigration constitutes contradictory attitudes towards identity documents. Officials imagine legal identity documents as legitimate and viable, and simultaneously compromised due to administrative corruption and complicity. This documentary doublethink engenders grave instability of citizenship status. The article illuminates how the rule of law – like the documentary regimes it sustains – is Janus-faced by producing and obscuring precarious citizenship.